1980
DOI: 10.5558/tfc56222-5
|View full text |Cite
|
Sign up to set email alerts
|

Personal Bias in Forest Measurements

Abstract: The assumption that measurement errors are negligible during a forest inventory was tested using forestry students. The magnitude of personal bias in measuring tree diameter at breast height (dbh), total height, and basal area Rer hectare was obtained. Bias was negligible in dbh measurements and the among-crew coefficient of variation (CV) was 8.16%. Heights were significantly underestimated and the among-crew CV was 21.86%. The percentage error in basal area Der hectare determination was 4.09% at the measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…Dbh is the most fundamental of tree measurements and is defined as the outside-bark-stem diameter of a tree at a point on the stem that is 1.3 m above the ground from the base of the tree [1,3]. In forestry, the word "diameter" implies that the trees would between several re-measurements of dbh and height have been reported for example in [32][33][34][35][36][37][38]. The results of these studies have been reported using various means (e.g., mean, absolute and relative standard deviation, and bias) and straightforward comparisons of the resulting precision are not possible in all cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dbh is the most fundamental of tree measurements and is defined as the outside-bark-stem diameter of a tree at a point on the stem that is 1.3 m above the ground from the base of the tree [1,3]. In forestry, the word "diameter" implies that the trees would between several re-measurements of dbh and height have been reported for example in [32][33][34][35][36][37][38]. The results of these studies have been reported using various means (e.g., mean, absolute and relative standard deviation, and bias) and straightforward comparisons of the resulting precision are not possible in all cases.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in [37], the author's own measurements of dbh and height were used as the true value in the study and were assumed to be error free when compared to measurements conducted by others, whereas Hyppönen and Roiko-Jokela [33] admitted that measurement bias could not be calculated since it was not possible to obtain the exact dbh. Furthermore, Kitahara et al [39] have noted that in tree height measurements, educated and experienced mensurationists provide more precise results than beginners with only basic knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…For example, when the range of / h H was from 0.00 to 0. Measuring tree diameter and height may be subject to errors, even though stand and tree variables are commonly assumed to be measured without error [42,43]. The measurement errors made by field crew or faulty instrument or both might be substantial [42].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the violation of the second assumption may lead to biased estimation of parameters and (or) of the standard errors of the parameters, and consequently to misleading the hypothesis test [44,45]. If the predictor variables in Equation (1) Measuring tree diameter and height may be subject to errors, even though stand and tree variables are commonly assumed to be measured without error [42,43]. The measurement errors made by field crew or faulty instrument or both might be substantial [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation